Musical Expertise and Executive Functions in Experienced Musicians - Edoardo Passarotto; Bruno Kopp; André Lee; Eckart Altenmüller (Brain Sciences, 2023)
Extensive music practice has been suggested to enhance the development of cognitive abilities over and above musical expertise. Executive functions (EFs) have been particularly investigated, given their generalizability across different domains and their crucial role in almost all aspects of cognition. However, the relationship between musical expertise and EFs is still not completely understood, as several studies have reported conflicting results. The present study aims to investigate the relationship between musical expertise and EFs, determining which facets—if any—of EFs might be particularly relevant to extensive music practice. Thirty-five student pianists completed a set of neuropsychological tasks which assessed EFs (the Trail Making Task, Design Fluency, Numerical Stroop, and the Tower of London). They also performed a short musical excerpt inspired by the piano literature. Musical expertise was assessed by considering three parameters, namely the highest academic degree in music, the lifetime amount of music practice, and the quality of the sample-based musical performance. The results indicate that postgraduate piano students did not show advantages in EFs compared to undergraduate piano students. More extensive lifetime practice in music was solely associated with faster visual reaction times on the Numerical Stroop task. The Trail Making and Design Fluency scores were significant predictors of the quality of the sample-based musical performance. In conclusion, the present data suggests that EFs and the amount of music practice do not seem to be correlated in student pianists. Nevertheless, some facets of EFs and the quality of musical performance may share substantial amounts of variance.